2005
DOI: 10.1016/j.theochem.2004.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational frequencies and structural determination of thiocyanogen

Abstract: The vibrational frequencies and corresponding normal mode assignments of thiocyanogen are examined theoretically using the Gaussian03 set of quantum chemistry codes. All normal modes were successfully assigned to one of six types of motion (CbN stretch, C-S stretch, S-S stretch, S-CbN bend, C-S-S bend, C-S-S-C torsion) utilizing the C 2 symmetry of the molecule. Molecular orbitals and bonding are examined. Published by Elsevier B.V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Instead, it resulted in the appearance of a new sharp ν­(CN) band at 2063 cm –1 (Figure , black line). This could be due to formation of free [NCS]¯ (the S–S bond is known to be weak), decomposition to form [CN]¯, or formation of the relatively long-lived [NCS] 2 •– . The UV–vis spectrum (Figure ) shows no evidence of [NCS] 2 •– that features a characteristic absorbance at 480 nm .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it resulted in the appearance of a new sharp ν­(CN) band at 2063 cm –1 (Figure , black line). This could be due to formation of free [NCS]¯ (the S–S bond is known to be weak), decomposition to form [CN]¯, or formation of the relatively long-lived [NCS] 2 •– . The UV–vis spectrum (Figure ) shows no evidence of [NCS] 2 •– that features a characteristic absorbance at 480 nm .…”
Section: Resultsmentioning
confidence: 99%
“…[NCS]¯ (the S-S bond is known to be weak 54 an OTTLE cell. Spectra: Red -parent [1] 3-, green -after the irreversible oxidation to producing (among others) (NCS)2 (λmax = 320 nm); black -after the back reduction of (NCS)2 producing mainly [Et4N]3 [3]).…”
Section: Electrochemical and Spectroelectrochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical absorption of disulfide bonds at 525 cm −1 was disappeared in cured resins. 56 The new absorption band at 683 cm −1 was attributed to the formation of C−S bonds. 56 These results indicated that disulfide bonds were involved in the polymerization of the system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The geometries of B 12 H 12 2− , 1 , and 2 were taken from the relevant crystal structures (CSD code FUYZOO for B 12 H 12 2− , ZASYEX for 1 , or this work for 2b ), while 2a and 2c geometries were built by analogy. The structure of (SCN) 2 was built according to ref .…”
Section: Methodsmentioning
confidence: 99%